2011
DOI: 10.1002/ajmg.a.33877
|View full text |Cite
|
Sign up to set email alerts
|

6q27 subtelomeric deletions: Is there a specific phenotype?

Abstract: We read with great interest the report of Mosca et al. [2010] in theMay issue of the Journal, describing a patient with a 5.65Mb deletion on chromosome 6q27 (ranging from 165.24Mb to the 6q telomere at 170.89 Mb)associated with intellectual disability and a Ehlers–Danlos (EDS) like phenotype. We would like to further delineate the phenotypic spectrum of these rearrangements by reporting two additional patients with this chromosomal abnormality. Patient 1 is a 17-year-old girl, with a history of moderate psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9]15,16 Though the clinical phenotypes associated with this deletion are quite variable, reports in unrelated subjects from independent investigators have shown that ACC, PNH, polymicrogyria, hydrocephalus, and cerebellar malformations are the consistently observed features. A recent analysis of a comprehensive map of loci for ACC from 374 patients revealed that chromosome 6q27 was one of the few loci wherein six or more subjects with ACC have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9]15,16 Though the clinical phenotypes associated with this deletion are quite variable, reports in unrelated subjects from independent investigators have shown that ACC, PNH, polymicrogyria, hydrocephalus, and cerebellar malformations are the consistently observed features. A recent analysis of a comprehensive map of loci for ACC from 374 patients revealed that chromosome 6q27 was one of the few loci wherein six or more subjects with ACC have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Structural brain malformations are consistently observed in these patients and include agenesis of the corpus callosum (ACC), periventricular nodular heterotopia (PNH), polymicrogyria, hydrocephalus, and cerebellar malformations. [1][2][3][4][5][6][7][8][9][10] Whereas previous studies have attempted to delineate the critical region responsible for brain malformations in patients with terminal 6q27 deletions, the sensitivity of the methodologies used has prevented the fine-mapping of the critical region. 1,6 A detailed genomic analysis of the subtelomeric chromosome 6q region would help identify the putative genes involved in the causation of brain malformations.…”
Section: Introductionmentioning
confidence: 99%
“…We also performed a literature review to evaluate the clinical and cytogenomic findings from 28 patients with a deletion of 6q26-q27. 12 13 14 15 16 17 18 19 20 21 22 23 24 25 From this series of 36 patients, we defined genotype–phenotype correlations from prenatal to postnatal stages and two critical regions with putative haploinsufficient genes and other candidate morbid genes. These results provided evidence for diagnostic interpretation, genetic counseling, and clinical management of patients with deletions of 6q26-q27.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have tried to correlate the distal deletion of chromosome 6q to a distinct clinical phenotype ( Stevenson et al, 2004 ; Bertini et al, 2006 ; Rigon et al, 2011 ; Zhou et al, 2014 ). Others have sought to identify the minimum deleted interval containing the critical genes responsible for the major clinical problems ( Eash et al, 2005 ; Rooms et al, 2006 ; Peddibhotla et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Others have sought to identify the minimum deleted interval containing the critical genes responsible for the major clinical problems ( Eash et al, 2005 ; Rooms et al, 2006 ; Peddibhotla et al, 2015 ). However, it is still very problematic to identify clinically patients carrying such deletion and to correlate deleted genes with a clinical phenotype ( Rigon et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%